2011
DOI: 10.4028/www.scientific.net/amr.324.427
|View full text |Cite
|
Sign up to set email alerts
|

Side Gate Graphene and AlGaN/GaN Unipolar Nanoelectronic Devices

Abstract: Three-terminal junction devices were realized in graphene grown heteroepitaxially on semiinsulating silicon carbide as well as in AlGaN/GaN heterostructures grown by MOCVD on sapphire containing a two dimensional electron gas. These nanoelectronic devices were fabricated using electron beam lithography. In both types of heterostructures room temperature electrical measurements revealed a pronounced nonlinear electrical behavior of the fabricated nanoelectronic devices. The obtained voltage rectification at roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…We have fabricated epitaxial graphene Y‐branch and T‐branch TTJs on semi‐insulating SiC substrates, ,] see Figure . A feature specific for our TTJs is that the terminal pads consist of graphene instead of a metal, i.e., the devices are metal‐free.…”
Section: Gnr Three Terminal Junctionsmentioning
confidence: 99%
“…We have fabricated epitaxial graphene Y‐branch and T‐branch TTJs on semi‐insulating SiC substrates, ,] see Figure . A feature specific for our TTJs is that the terminal pads consist of graphene instead of a metal, i.e., the devices are metal‐free.…”
Section: Gnr Three Terminal Junctionsmentioning
confidence: 99%
“…The relative simple fabrication requirements and implementation abilities into post CMOS circuits make them attractive for future low power high speed electronics. TTJ devices were mainly demonstrated on III-V heterostructures [2,5,6], Recently, voltage rectification was demonstrated on exfoliated graphene [7] and epitaxial graphene [8,9]. In this report voltage rectification of two TTJ device types fabricated on epitaxial graphene grown on semiinsulating silicon carbide will be shown.…”
Section: Introductionmentioning
confidence: 81%
“…The T-or Y-shaped junctions belong to the device group of three-terminal junctions (TTJ) exploiting specific effects of the carrier transport of two dimensional electron and hole gases in lateral confined channels. Recently, it was shown that the initially predicted nonlinear transport behavior leading to rectification is not an exclusive consequence of ballistic or diffusive ballistic transport, but can also appear at pure diffusive transport conditions [1,2] or due to differences in charge transfer through the metal graphene contact [3]. For graphene TTJ rectification [3][4][5], frequency multiplication [5] and inverters [6] in Y-or T-shape junctions were demonstrated.…”
Section: Introductionmentioning
confidence: 99%